TRATADO DE LIBRE COMERCIO ENTRE PERÚ Y CANADÁ (ALCANCES Y PERSPECTIVAS) - Ugarte Casafranca, Walter (2008)
This article examines the Free Trade Agreement between Peru and Canada. Research on the background of the negotiations, the importance of the Canadian market in the Peruvian economy and the possible impact it has to have this trade agreement. It includes an analysis of the trade indicators and an interpretation of the agreement for the promotion and reciprocal protection of investments Peru-Canada.